Consensus Recommendations on the Prehospital Care of the Injured Athlete With a Suspected Catastrophic Cervical Spine Injury. Issue 4 (July 2020) - Mills, Brianna M.; Conrick, Kelsey M.; Anderson, Scott; Bailes, Julian; Boden, Barry P.; Conway, Darryl; Ellis, James; Feld, Francis; Grant, Murphy; Hainline, Brian; Henry, Glenn; Herring, Stanley A.; et al.
Abstract : Introduction: Sports participation is among the leading causes of catastrophic cervical spine injury (CSI) in the United States. Appropriate prehospital care for athletes with suspected CSIs should be available at all levels of sport. The goal of this project was to develop a set of best-practice recommendations appropriate for athletic trainers, emergency responders, sports medicine and emergency physicians, and others engaged in caring for athletes with suspected CSIs. Methods: A consensus-driven approach (RAND/UCLA method) in combination with a systematic review of the available literature was used to identify key research questions and develop conclusions and recommendations on the prehospital care of the spine-injured athlete. A diverse panel of experts, including members of the National Athletic Trainers' Association, the National Collegiate Athletic Association, and the Sports Institute at UW Medicine participated in 4 Delphi rounds and a 2-day nominal group technique (NGT) meeting. The systematic review involved 2 independent reviewers and 4 rounds of blinded review. Results: The Delphi process identified 8 key questions to be answered by the systematic review. The systematic review comprised 1544 studies, 49 of which were included in the final full-text review. Using the results of the systematic review as a shared evidence base, the NGT meeting created and refined conclusions and recommendations until consensus was achieved. Conclusions: These conclusions and recommendations represent a pragmatic approach, balancing expert experiences and the available scientific evidence.